Characterization of Soiling Bands on the Bottom Edges of PV Modules - Cui, Yong-Qin; Xiao, Jian-Hua; Xiang, Jin-Li; Sun, Jia-Huan (Frontiers in Energy Research, 2021)
Soiling of photovoltaic (PV) modules, especially non-uniform soiling, can lead to PV power loss. For example, soiling bands at the bottom edge of framed modules are caused by the accumulation of water and dirt at a lower tilt angle. However, few studies have investigated this issue. In this study, industrial and commercial metal rooftop PV power stations in central and eastern China were investigated, with a focus in Xi’an and Kaifeng cities. The results show that (1) soiling bands were widespread, even in Guangzhou city, where annual rainfall is approximately 1,800 mm; (2) soiling bands were found during every month in Xi’an city, even from July to September when heavy rainfall occurs frequently; (3) three types of soiling bands were observed on modules (rectangular, transverse trapezoidal, and triangular), with double triangular, arch, and shallow U-shape types also being observed in land-scape-oriented modules; (4) the mean relative difference of the maximum direct current due to soiling bands between one maximum power point tracking system and its control from June 19 to October 2, 2019 in Kaifeng city was approximately 4.7%.